Traffic signal control evaluation development based on simulation testbed - Lim, Wei Yang (Nanyang Technological University, 2024)
The project aims to develop a comprehensive evaluation system for traffic signal control systems based on a simulation testbed created in SUMO. The project will focus on handling the provided simulation testbed and developing the evaluation system using Python.